Application Of Dempster Shafer Method To Diagnose Disease In Sugarcane Plant - Dewi Novika Simanjuntak; Fristi Riandari (Journal of Intelligent Decision Support System (IDSS), 2021)
Sugarcane is a very important and agrarian plantation product in Indonesia, because sugar cane is a producer of sugar. However, in its cultivation, several problems often occur, such as diseases in sugarcane plants where when sugarcane plants are attacked by disease and are not handled, farmers will experience crop failure. Based on this, a tool is needed in the form of an expert system to diagnose diseases in sugarcane plants. The method used in this study is the Dempster Shafer method which processes data by providing evidence based on the belief funcation and plausible value of each symptom. This study treats 4 types of disease with 13 symptoms. The results showed that the dempster shafer method can be used as a tool in diagnosing sugarcane plant diseases so that it is expected to help farmers in handling diseases that attack sugarcane plants quickly and precisely and can increase profits from sugarcane harvests for farmers.